The Comparison of treated coco-husk composite and its applications in architectural interior - Erni Setyowati; Edward E. Pandelaki; Edy Supriyo (E3S Web of Conferences, 2018)
This research highlights the acoustical behavior comparison of treated coco-husk fibre reinforced polyesther resin (FRP) on four different treatments. The FRP made of materials with composition of polyesther resin, coco-husk fibre and catalyst as 200 ml, 25 grams and 20 ml respectively. After mixed, the dough was then poured into tabular moulding with 30 mm in diameter. The mouldings were then dismantled and shaped into two thickness groups, two samples in 15 mm and 30 mm for the rest. The method used for this study is the absorption coefficient test refer to the ASTM E-1050-98 with Bruer & Kjaer 4206 impedance tube completed with its pulse- LAN XI utilization. The result is that the best performance was showed by the coco-husk FRP with 15 mm diameter treated with eight half wavelength resonators and additional 10 mm cavity. The sound absorption resulted appeared in wide broadband frequencies comparing to other treated samples. The sound absorption peak reached up to 0.98 at 2.25kHz. This result would be a good address for the interior absorber material for building purposes as described in the end of this paper.